2021
DOI: 10.1186/s12888-021-03101-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of the 12-item WHODAS-2.0 in a naturalistic sample of outpatients with psychotic disorders

Abstract: Background The World Health Organization Disability Assessment Schedule 2.0 (WHODAS-2.0) is a self-administered instrument to assess functional impairment. It is used in the general population as well as different patient groups. However, its application to patients with psychotic disorders may be hampered by disease-specific difficulties of self-estimation. This study aimed to examine the psychometric properties of the short (12-item) WHODAS-2.0 in a naturalistic sample of outpatients attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…11 Of particular interest for this population and the current study, the previous validation study showed that patients who were rated low on psychotic symptom severity generally also self-assessed as having lower functional impairments. 11 This indicates that the instrument accounts for psychotic symptomology.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…11 Of particular interest for this population and the current study, the previous validation study showed that patients who were rated low on psychotic symptom severity generally also self-assessed as having lower functional impairments. 11 This indicates that the instrument accounts for psychotic symptomology.…”
Section: Methodsmentioning
confidence: 77%
“…At a few outpatient units, we also had information about patients' functioning, assessed using the 12 item World Health Organization Disability Assessment Schedule 2.0 (WHODAS-2.0), a self-administered questionnaire. 11 This is a general assessment instrument that can be used in both patient and general population settings and has been cross-culturally validated both in patients with mental disorders and in those with somatic disorders. 12 The questionnaire contains two items corresponding to each domain of functioning (cognition, mobility, household, self-care, social and society), and the domains are directly linked to disability concepts according to the International Classification of Functioning, Disability and Health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a recent study from our group showed the WHODAS 2.0 to adequately measure disability aspects in both severe and common mental disorders [ 43 ]. Moreover, in an independent sample of outpatients with psychotic disorders the WHODAS 2.0 total score showed good reliability (Cronbach’s α = 0.89) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Spanish version [ 46 ] of the Positive and Negative Syndrome Scale (PANSS) [ 44 ] was used to rate severity of five symptomatic dimensions, namely positive, negative, disorganization, mania and depression, based on a previous consensus of PANSS factor analysis studies [ 47 ].…”
Section: Methodsmentioning
confidence: 99%